Regulation of allergen-specific immune responses by CD4+ CD45R+ cells in patients with allergic contact dermatitis - Baxevanis, C. N.; Papadopoulos, N. G.; Katsarou-Katsari, A.; Papamichail, M. (J Allergy Clin Immunol, 1994)
Circulating T lymphocytes from 20 patients with an immediate patch test reaction were tested for proliferative responses in vitro to contact allergens during both immediate and delayed skin reactions. T lymphocytes collected during the immediate patch test reaction responded specifically in the challenge allergens in the presence of autologous monocytes. Subset analysis revealed that the proliferation pattern was dominated by the CD4+ CD29+ T-cell subpopulation, whereas CD8+ or CD4+ CD45R+ cells did not respond. A similar pattern in T-cell subset proliferation was observed when cells were collected during a positive delayed skin reaction. In contrast, in the case of a negative delayed skin reaction, proliferative responses of lymphocytes to the specific allergens were dominated by CD45+ cells. The latter T-lymphocyte subset could greatly suppress in an allergen-specific manner the proliferation of CD29+ autologous cells. The in vitro allergen-specific proliferation of CD29+ or CD45R+ cells was restricted by the major histocompatibility complex class II (HLA-DR) gene products. It is suggested that allergen-specific immune responses take place in the induction and evolution of an immediate patch test reaction into a delayed one.
Keywords: Adult Allergens Antibodies Antibody Formation Antigens; Allergic Contact Epitopes Female HLA-DR Antigens Humans Integrins Male Middle Aged Monocytes Patch Tests T-Lymphocytes; CD Antigens; CD29 Antigens; CD4 Antigens; CD45 Cell Division Dermatitis